2020
DOI: 10.24275/rmiq/alim936
|View full text |Cite
|
Sign up to set email alerts
|

Effect of processing parameters on astaxanthin nanoemulsions with stearic acid using ultrasonic emulsification

Abstract: Modelado de la biodegradación en biorreactores de lodos de hidrocarburos totales del petróleo intemperizados en suelos y sedimentos (Biodegradation modeling of sludge bioreactors of total petroleum hydrocarbons weathering in soil and sediments)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…According to Figure , AOA shows a reduction in 6.56% activity compared to that of a fresh sample. This statement is supported by Flores-Miranda et al, who reported a 50% reduction in the antioxidant activity of astaxanthin-encapsulated nanoemulsions over a period of 28 days compared to that of a fresh sample. Figure also shows an 8.4% reduction in emulsion stability compared to that of a fresh sample.…”
Section: Resultsmentioning
confidence: 97%
“…According to Figure , AOA shows a reduction in 6.56% activity compared to that of a fresh sample. This statement is supported by Flores-Miranda et al, who reported a 50% reduction in the antioxidant activity of astaxanthin-encapsulated nanoemulsions over a period of 28 days compared to that of a fresh sample. Figure also shows an 8.4% reduction in emulsion stability compared to that of a fresh sample.…”
Section: Resultsmentioning
confidence: 97%
“…On the other hand, liposomes have been used in the treatment of osteoarthritis, but there is no literature on the evaluation of the effect of astaxanthin-loaded liposomes on bone health. Previous studies have indicated that the biological efficacy of the astaxanthin extracts may change with the manner of storage and extraction [1,21]. In the present study, astaxanthin (asta)-loaded liposomes prepared using soybean phosphatidylcholine (SPC) were expected to maintain the bioactivity of the astaxanthin extract and increase the absorption rate in the bone cells.…”
Section: Introductionmentioning
confidence: 86%
“…Oil-in-water nanoemulsions and microemulsions are two basic colloidal dispersion systems suitable for the delivery of lipophilic β-carotene for food applications. The literature also reports several techniques for the preparation of micro/nanoemulsions, such as emulsion phase inversion [292], high-pressure homogenization [293], microfluidization [144,294], supercritical fluid methods [145,295], spontaneous emulsification [296] and phase-inversion temperature [297].…”
Section: Micro/nanoemulsionsmentioning
confidence: 99%